PARTISIPASI PEMILIH MASYARAKAT PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA TANGERANG SELATAN TAHUN 2020 - Toni Anwar Mahmud (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT Stipulation of Law of the Republic of Indonesia Number 6 of 2020 concerning Stipulation of Government Regulations in Lieu of Law Number 2 of 2020 concerning Third Amendments to Law Number 1 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning Election of Governors, Regents , and the Mayor Becomes Law Becomes Law on August 11, 2020, has stipulated that the simultaneous regional elections in 2020 will be held on December 9, 2020, even though the Covid-19 pandemic is ongoing and there are significant additional positive cases. This research uses a qualitative approach and uses literature study. The results of this study show that there is an increase in voter participation in the 2020 elections for South Tangerang City compared to the 2020 elections, which amounted to 3.06%. The total voter turnout for the 2020 elections was 594,711 voters consisting of 575,725 valid votes, 18,986 invalid votes. The people of South Tangerang City who exercised their voting rights were only 60.93% of the 976,019 DPT stipulated by the South Tangerang City KPU or 381,308 (39.07%) South Tangerang City voters did not exercise their voting rights. Meanwhile, in the 2015 regional elections, voter participation was 57.87% with a total number of voters of 920,115 people and users of voting rights as many as 533,444 people. Keywords: Role of Parents, Forming Character, Globalization Era